Analisis Kadar Nikotin dalam Tembakau Tongka Kabupaten Bantaeng - Maria, Tumbel (bionature, 2010)
This research aim to to know nicotine rate which implied in processed tongka tobacco simply in District Bantaeng, because the tobacco don't have lable. This Research benefit to give information at society; what nicotine rate in tongka tobacco within measure to be consumed or not. Nicotine have toksis; besides can addictive or depended also can generate is cancercous. Determining rate nicotine can do it with Titration Asidimetri method. Sampel research consist tobacco which circulate in four market in District Bantaeng. Pursuant to result of research, tongka tobacco nicotine rate which circulate in Lambocca' Market 1,92%, Induk market 1,79%, Dampang market 1,67% and Banyorang market 1,50%. The Nicotine rate altogether smaller than enabled by Industrial Standard of Indonesia that is 2%.